Determination of tetramethylthiuram disulfide (thiram) for residual analysis in food using spectrophotometry coupled with a solid-phase reactor (SPR) in a flow system - Silva Junior, Ranulfo C. [UNESP]; Kushikawa, Ricardo T. [UNESP]; Gomes, Homero M. [UNESP]; Teixeira, Marcos F. S. [UNESP] (Taylor & Francis Ltd, 2014)
An analytical method was developed for quantification of the fungicide thiram (tetramethylthiuram disulfide), based on its capacity to complex Cu2+ ions. A solid-phase reactor (SPR) was coupled in a flow system containing a spectrophotometer as detector. The SPR consisted of a tube filled with finely ground resin, in which copper(II) phosphate was immobilised prior to polymerisation. Contact of thiram with the Cu2+ ions immobilised in the resin resulted in the formation of a strongly coloured Cu2+/thiram complex. Maximum absorbance of the Cu2+/thiram complex was obtained at a wavelength of 439 nm. The usefulness of the methodology has been evidenced by the determination of thiram residues in corn and bean grains. Previously, a variety of transition metal cations which would form coloured complexes with tetramethylthiuram disulfide were tested.
Keywords: flow injection analysis; spectrophotometry; solid-phase reactor; thiram; thiuram disulfide